Pengaruh Kualitas Layanan terhadap Loyalitas Pelanggan melalui Kepuasan sebagai Variabel Intervening pada Swalayan Pamella Enam Yogyakarta - Ova Pasianus; Any Agus Kana (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
Retail business is a business which sells goods and services. This business prioritizes service quality and customer satisfaction to get loyalty from the customer. This study was conducted in PamellaEnam Yogyakarta from December 2019 up to January 2020. This study aimed to analyze the effect of service quality on customer loyalty through customer satisfaction as an intervening variable. Samples were taken with a Non-probability Sampling Method and a Purposive Sampling Technique. The number of the samples is 166 people.All of the 166 people are customers who have made transactions at least three times in Pamela Enam. Secondary data obtained from Government and non-Governmental publications. Primary data were collected using a questionnaire as the instrument. Google form was used as a media to collect the data. All the data, instrument, and results are valid and reliable. The data were analyzed using a path analysis with IBM SPSS 22.00 software with σ= 5%. The Sobel Test was conducted to decide the indirect effect of service quality on customer loyalty through customer satisfaction. The results of the Sobel Test show that customer satisfaction has a significant indirect effect. The results of the path analysis show that: service quality and customer satisfaction have a direct effect on customer loyalty and; service quality has a direct effect on customer satisfaction.